ANALISIS PENCARIAN DATA SMARTPHONE MENGGUNAKAN NIST UNTUK PENYELIDIKAN DIGITAL FORENSIK - Riya Majalista; Tata Sutabri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
This study is based on the number of crimes that occur in cyberspace. This research looks at what smartphone data cybercriminals typically obtain. The application of digital developments in forensics supports the resolution of some cases of cybercrime. Forensic Information Systems are commonly used to solve cybercrime cases. This digital forensics technique works by weighing the information that is used as the basis for developing a cybercrime case. The goal is to make it available as a basis for forensic science to be used. Keywords : NIST, digital forensic, cybercrime